Development of Verbal Creativity Test Based on Creative Industry Sectors - Suyasa, P. Tommy Y. S.; Setyawan, Ignatius Roni; Rahaditya, R.; Jessyca, Jessyca; Rae, Olivia Beatrix; Fahditia, Amala (National Research and Innovation Agency, Indonesia, 2025)
TThis study aims to assess the validity and reliability of the verbal creativity test developed in order to identify the creative potential of prospective public relations practitioners who will be tasked with developing and promoting Indonesia’s creative industries. The test developed was named VCT - ICI, which is an abbreviation for Verbal Creativity Test - Indonesian Creative Industries (Tes Kreativitas Verbal - Industri Kreatif Indonesia). This test was structured based on 16 subsectors of Indonesia’s creative industries, which were used as a stimulus in designing test items. The respondents in this study were 201 students majoring in public relations of the faculty of communication sciences from three Indonesia’s universities. Data analysis was carried out to assess the validity and reliability of the verbal creativity test developed. Further analysis produces norms (standard scores) for interpreting the verbal creativity measurement results.